High-voltage-resistant composite solid electrolyte as well as preparation method and application thereof

By using poly(vinylidene fluoride-co-hexafluoropropylene) and other materials to prepare high-voltage composite solid electrolytes, the safety hazards and electrochemical decomposition of organic liquid electrolytes in lithium-ion batteries are solved, and efficient ion conduction and circulation are achieved Stability, suitable for the combination of high-voltage positive electrode and lithium metal in lithium-ion batteries.

CN119230951AInactive Publication Date: 2024-12-31ZHONGBEI UNIV +1

Patent Information

Application Number
CN202411527205.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2024-12-31
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The organic liquid electrolytes used in existing lithium-ion batteries have safety risks of explosive and flammable, and are prone to electrochemical decomposition when in contact with high-voltage positive electrode materials, limiting the development of lithium batteries.

Method used

High-pressure-resistant composite solid electrolyte is prepared by materials such as poly(vinylidene fluoride-co-hexafluoropropylene), polyethylene glycol diacrylate and zwitter polyionic liquid monomers. The chemical environment of the electrolyte is improved through the crosslinking structure and the crystallization is regulated. , improves electrochemical window and ion conductivity, and can be used with high-voltage positive electrode and lithium metal.

Benefits of technology

It realizes efficient ion conduction in the 1.5-5.4V electrochemical window, with ion migration reaching 55-80%, ion conductivity reaching 0.5×10-4-9.9×10-4S/cm, and at room temperature and extremely low temperature environments Excellent cycle stability was shown in the middle, with a capacity retention rate of more than 65%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230951A_ABST
    Figure CN119230951A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of solid-state electrolyte, and provides high-voltage-resistant composite solid-state electrolyte as well as a preparation method and application thereof. The preparation method comprises the following steps: mixing a polymer, an inorganic filler, a lithium salt and a solvent to obtain a precursor solution, mixing the precursor solution, a cross-linking agent and an initiator to obtain a reaction solution, and curing the reaction solution; the species of polymers are defined. The chemical environment of the electrolyte is improved and the crystallinity of the polymer is regulated and controlled through the cross-linked structure of the polymer, so that the electrochemical window and the ionic conductivity of the composite solid electrolyte are improved, and the composite solid electrolyte can work between 1.5 V and 5.4 V and is matched with a high-voltage positive electrode and lithium metal for use; excellent cycling stability can be shown at room temperature and even in an extremely low-temperature environment; the amphoteric polyionic liquid monomer is used as a polymer matrix, so that enough mechanical strength is ensured, an efficient and stable Li < + > channel can be formed, and the ionic conductivity is relatively high at room temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid electrolytes, and in particular to a high-voltage resistant composite solid electrolyte and a preparation method and application thereof. Background Art

[0002] With the development of society, people's demand for energy is increasing. In order to solve problems such as energy shortage, resource depletion, and environmental degradation, people are in urgent need of finding clean and renewable energy. Lithium-ion batteries have the advantages of high energy density, high power density, and long cycle life, and have been widely used in electric vehicles, smart grids, and electronic products. At present, many commercial lithium batteries use organic liquid electrolytes, which are flammable and have risks such as explosion and combustion, and cannot meet the safety requirements. In addition, organic liquid electrolytes also have interface problems, such as the formation of lithium crystals causing short circuits, increased interface resistance, and poor battery performance caused by side reactions between interfaces. Solid electrolytes have the advantages of good safety performance, high energy density, good electrochemical stability, long cycle life, and good low-temperature performance, and have attracted widespread attention.

[0003] Solid electrolytes are divided into inorganic solid electrolytes, organic polymer solid electrolytes and composite solid electrolytes. Among them, organic polymer solid electrolytes have the advantages of high ion conductivity, simple preparation process and good flexibility, and are regarded as one of the research hotspots. However, organic polymer solid electrolytes are not suitable for high-voltage positive electrode materials (such as LiNi 0.6 Mn 0.2 Co 0.2 O2, NCM622), electrochemical decomposition is likely to occur, which will reduce battery performance and create safety hazards, limiting the development of solid-state lithium batteries.

[0004] Therefore, research and development of new polymer composite solid electrolytes with excellent ionic conductivity, high electrochemical stability and good mechanical properties are of great significance to promoting the advancement of lithium-ion batteries, which will not only help promote the popularization of electric vehicles, but also help reduce dependence on fossil fuels, reduce greenhouse gas emissions, and achieve the goals of environmental protection and sustainable development. Summary of the invention

[0005] The purpose of the present invention is to provide a high-voltage resistant composite solid electrolyte and a preparation method and application thereof in view of the deficiencies in the prior art.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a high-voltage resistant composite solid electrolyte, comprising the following steps:

[0008] (1) mixing a polymer, an inorganic filler, a lithium salt and a solvent to obtain a precursor solution;

[0009] (2) mixing a precursor solution, a cross-linking agent and an initiator to obtain a reaction solution;

[0010] (3) solidifying the reaction solution to obtain a high-voltage resistant composite solid electrolyte;

[0011] The polymer comprises one or more of poly(vinylidene fluoride-co-hexafluoropropylene), polyethylene glycol diacrylate and amphoteric polyionic liquid monomers.

[0012] Preferably, the inorganic filler comprises one or more of a lithium lanthanum zirconium oxide solid electrolyte, a lithium lanthanum titanate solid electrolyte, and a lithium lanthanum zirconium tantalum oxide solid electrolyte;

[0013] The lithium salt comprises one or more of lithium perchlorate, lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium trifluoromethanesulfonate and lithium bis(trifluoromethanesulfonylimide);

[0014] The solvent is dimethyl sulfoxide, tetrahydrofuran, N-methylpyrrolidone, N,N-dimethylformamide or acetonitrile;

[0015] The crosslinking agent is ethoxylated trimethylolpropane triacrylate, N,N-methylenebisacrylamide or 2-phenoxyethyl acrylate;

[0016] The initiator is azobisisobutyronitrile.

[0017] Preferably, the mass volume ratio of the polymer and the solvent is 1g:1-20mL, the mass ratio of the polymer and the inorganic filler is 1-20:1, the mass ratio of the polymer and the lithium salt is 1-10:1, the mass ratio of the polymer and the cross-linking agent is 70-85:1, and the mass ratio of the polymer and the initiator is 20-30:1.

[0018] Preferably, the curing temperature in step (3) is 60-80° C., and the curing time is 1.5-6 hours.

[0019] Preferably, the structural formula of the amphoteric polyionic liquid monomer is:

[0020] Wherein, R1 is a carbon chain having 1 to 10 carbon atoms; R2 is a carbon chain having 1 to 10 carbon atoms or hydrogen.

[0021] Preferably, the method for preparing the amphoteric polyionic liquid monomer comprises the following steps:

[0022] 1) mixing alkyl sultone and toluene to obtain a solution I;

[0023] Mixing 1-vinylimidazole and acetonitrile to obtain solution II;

[0024] 2) adding solution I dropwise to solution II to react and obtain a solid product;

[0025] 3) Drying the solid product to obtain the amphoteric polyionic liquid monomer.

[0026] Preferably, in step 1), the mass volume ratio of the alkyl sultone and toluene is 10-20 g: 5-13 mL, and the mass volume ratio of the 1-vinylimidazole and acetonitrile is 5-15 g: 30-40 mL; and in step 2), the volume ratio of the solution I and the solution II is 5-13: 30-40.

[0027] Preferably, the dripping speed in step 2) is 0.3 to 1 drop / s; the reaction temperature is 45 to 60°C, the reaction time is 1.5 to 3 hours, stirring is performed during the reaction, and the stirring speed is 500 to 600 r / min; the drying temperature in step 3) is 50 to 60°C, and the drying time is 24 to 48 hours.

[0028] The present invention also provides a high-voltage composite solid electrolyte prepared by the preparation method, wherein the thickness of the high-voltage composite solid electrolyte is 200 to 500 μm.

[0029] The present invention also provides application of the high-voltage resistant composite solid electrolyte in lithium ion batteries.

[0030] The beneficial effects of the present invention include the following:

[0031] 1) The present invention improves the chemical environment of the electrolyte through the cross-linked structure of the polymer, regulates the crystallinity of the polymer, and thereby improves the electrochemical window and ion conductivity of the composite solid electrolyte, so that it can operate between 1.5 and 5.4 V, the ion migration number reaches 55 to 80%, and the ion conductivity reaches 0.5×10 -4 ~9.9×10 -4 S / cm, and can be used with high-voltage cathodes and lithium metals. It can show excellent cycle stability at room temperature and even in extremely low temperature environments. The capacity retention rate after 300 cycles at 25°C and 0.2C is higher than 65%;

[0032] 2) The present invention uses amphoteric polyionic liquid monomers as the polymer matrix of the solid electrolyte, which not only ensures sufficient mechanical strength, but also forms an efficient and stable Li + The channel has high ion conductivity even at room temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The electrochemical window of the high-voltage composite solid electrolyte prepared in Examples 1, 2 and 4;

[0034] Figure 2 This is a cycle performance diagram at 25°C and 0.2C when the high-voltage composite solid electrolyte prepared in Example 2 is used in a lithium-ion battery NCM622;

[0035] Figure 3 This is a cycle performance diagram of the high-voltage composite solid electrolyte prepared in Example 3 when used in a lithium iron phosphate battery at 25°C and 0.2C. DETAILED DESCRIPTION

[0036] The present invention provides a method for preparing a high-voltage resistant composite solid electrolyte, comprising the following steps:

[0037] (1) mixing a polymer, an inorganic filler, a lithium salt and a solvent to obtain a precursor solution;

[0038] (2) mixing a precursor solution, a cross-linking agent and an initiator to obtain a reaction solution;

[0039] (3) solidifying the reaction solution to obtain a high-voltage resistant composite solid electrolyte;

[0040] The polymer comprises one or more of poly(vinylidene fluoride-co-hexafluoropropylene), polyethylene glycol diacrylate and amphoteric polyionic liquid monomers.

[0041] In the present invention, the inorganic filler preferably comprises one or more of a lithium lanthanum zirconium oxide solid electrolyte, a lithium lanthanum titanate solid electrolyte, and a lithium lanthanum zirconium tantalum oxide solid electrolyte;

[0042] The lithium salt preferably comprises one or more of lithium perchlorate, lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium trifluoromethanesulfonate and lithium bis(trifluoromethanesulfonylimide);

[0043] The solvent is preferably dimethyl sulfoxide, tetrahydrofuran, N-methylpyrrolidone, N,N-dimethylformamide or acetonitrile;

[0044] The crosslinking agent is preferably ethoxylated trimethylolpropane triacrylate, N,N-methylenebisacrylamide or 2-phenoxyethyl acrylate;

[0045] The initiator is preferably azobisisobutyronitrile.

[0046] In the present invention, the mass volume ratio of the polymer and the solvent is preferably 1g:1-20mL, more preferably 1g:4-16mL, and more preferably 1g:6-14mL; the mass ratio of the polymer and the inorganic filler is preferably 1-20:1, more preferably 3-15:1, and more preferably 7-10:1; the mass ratio of the polymer and the lithium salt is preferably 1-10:1, more preferably 2-7:1, and more preferably 3-5:1; the mass ratio of the polymer and the cross-linking agent is preferably 70-85:1, more preferably 74-81:1, and more preferably 78:1; the mass ratio of the polymer and the initiator is preferably 20-30:1, more preferably 24-27:1, and more preferably 25:1.

[0047] In the present invention, the polymer is preferably a polymer after drying, and the drying temperature is preferably 50 to 60° C., more preferably 55° C.; the drying time is preferably 12 to 24 hours, more preferably 18 hours.

[0048] In the present invention, the inorganic filler is preferably an inorganic filler obtained by sequentially ball milling, drying and calcining. The ball milling is preferably wet ball milling, and the solvent used in the wet ball milling is preferably isopropanol. The mass volume ratio of the inorganic filler and isopropanol is preferably 1g:50-70mL, and more preferably 1g:60mL; the rotation speed of the ball mill is preferably 700-900r / min, and more preferably 800r / min; the ball milling time is preferably 12-24h, and more preferably 20h; the drying temperature is preferably 50-70°C, and more preferably 60°C; the drying time is preferably 8-16h, and more preferably 12h; the calcination temperature is preferably 650-750°C, and more preferably 700°C; the calcination time is preferably 8-24h, and more preferably 16h.

[0049] In the present invention, the mixing in step (1) is preferably ultrasonic mixing, and the frequency of ultrasonic mixing is preferably 30 to 45 kHz, more preferably 35 to 40 kHz; the time of ultrasonic mixing is preferably 4 to 24 hours, more preferably 10 to 16 hours.

[0050] In the present invention, stirring is preferably performed during the mixing process in step (2), and the stirring speed is preferably 500 to 600 r / min, more preferably 550 r / min; the stirring time is preferably 0.5 to 2 h, more preferably 1 h.

[0051] In the present invention, the curing in step (3) is preferably performed by dripping the reaction solution onto the positive electrode material and then curing; the dripping rate is preferably 0.1 to 1 drop / s, and more preferably 0.5 to 0.8 drop / s.

[0052] In the present invention, the curing in step (3) is preferably in-situ polymerization curing, and the temperature of the in-situ polymerization curing is preferably 60 to 80°C, more preferably 65 to 75°C, and more preferably 70°C; the time of the in-situ polymerization curing is preferably 1.5 to 6h, more preferably 3 to 5h, and more preferably 4h.

[0053] In the present invention, the structural formula of the amphoteric polyionic liquid monomer is:

[0054] Among them, R1 is preferably a carbon chain with 1 to 10 carbon atoms, and more preferably a carbon chain with 3 to 7 carbon atoms; R2 is preferably a carbon chain with 1 to 10 carbon atoms or hydrogen, and more preferably a carbon chain with 3 to 7 carbon atoms.

[0055] In the present invention, the method for preparing the amphoteric polyionic liquid monomer preferably comprises the following steps:

[0056] 1) mixing alkyl sultone and toluene to obtain a solution I;

[0057] Mixing 1-vinylimidazole and acetonitrile to obtain solution II;

[0058] 2) adding solution I dropwise to solution II to react and obtain a solid product;

[0059] 3) Drying the solid product to obtain the amphoteric polyionic liquid monomer.

[0060] In the present invention, the structural formula of the alkyl sultone in step 1) is: Among them, R1 is preferably a carbon chain with 1 to 10 carbon atoms, and more preferably a carbon chain with 3 to 7 carbon atoms; R2 is preferably a carbon chain with 1 to 10 carbon atoms or hydrogen, and more preferably a carbon chain with 3 to 7 carbon atoms;

[0061] The structural formula of the 1-vinylimidazole is:

[0062] In the present invention, the mass volume ratio of the alkyl sultone and toluene in step 1) is preferably 10-20 g: 5-13 mL, more preferably 13-18 g: 7-11 mL, and more preferably 15 g: 9 mL; the mass volume ratio of the 1-vinylimidazole and acetonitrile is preferably 5-15 g: 30-40 mL, more preferably 8-12 g: 33-38 mL, and more preferably 10 g: 35 mL; the volume ratio of the solution I and the solution II in step 2) is preferably 5-13: 30-40, more preferably 7-11: 33-38, and more preferably 9: 35.

[0063] In the present invention, the dripping speed in step 2) is preferably 0.3 to 1 drop / s, more preferably 0.5 to 0.8 drop / s, and more preferably 0.7 drop / s; the reaction temperature is preferably 45 to 60°C, and more preferably 50 to 55°C; the reaction time is preferably 1.5 to 3h, and more preferably 2 to 2.5h; stirring is preferably performed during the reaction, and the stirring speed is preferably 500 to 600r / min, and more preferably 550r / min; the drying temperature in step 3) is preferably 50 to 60°C, and more preferably 53 to 58°C, and more preferably 55°C; the drying time is preferably 24 to 48h, and more preferably 30 to 40h, and more preferably 34h.

[0064] In the present invention, in step 3), the solid product is preferably washed and filtered in sequence and then dried; the reagent used for the washing is preferably water, and the number of washings is preferably 2 to 4 times, and more preferably 3 times; the pressure of the filtration is preferably 0.04 to 0.1 MPa, and more preferably 0.06 to 0.08 MPa; the filtration time is preferably 1 to 2 min, and more preferably 1.5 min.

[0065] The present invention also provides a high-voltage composite solid electrolyte prepared by the preparation method. The thickness of the high-voltage composite solid electrolyte is preferably 200 to 500 μm, more preferably 250 to 400 μm, and more preferably 300 to 380 μm.

[0066] The present invention also provides application of the high-voltage resistant composite solid electrolyte in lithium ion batteries.

[0067] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0068] In an embodiment of the present invention, the preparation method of the amphoteric polyionic liquid monomer is:

[0069] Alkyl sultone and toluene in a mass volume ratio of 15 g:9 mL were mixed to obtain solution I; 1-vinyl imidazole and acetonitrile in a mass volume ratio of 10 g:35 mL were mixed to obtain solution II; solution I was added dropwise to solution II (the volume ratio of solution I to solution II was 9:35) at a rate of 0.7 drops / s, and the mixture was stirred at 55°C and 550 r / min for 2 hours to obtain a solid product; the solid product was washed three times with deionized water, filtered at 0.08 MPa for 1.5 minutes, and then dried at 55°C for 34 hours to obtain a zwitterionic polyionic liquid monomer.

[0070] The structural formula of alkyl sultone is:

[0071] The structural formula of the amphoteric polyionic liquid monomer is: Among them, R1 is CH2 and R2 is H.

[0072] Example 1

[0073] 0.11 g of lithium lanthanum zirconium tantalum oxide solid electrolyte (LLZTO) was placed in a ball mill, 6.6 mL of isopropanol was added, and wet ball milling was performed at a speed of 800 r / min for 20 h; the ball-milled material was first placed in a vacuum drying oven (vacuum degree of 1 bar) at 60°C for 12 h, and then calcined at 700°C for 16 h to obtain an inorganic filler.

[0074] 0.27 g of poly(vinylidene fluoride-co-hexafluoropropylene) (molecular weight 45500 Da) was dried at 55° C. for 18 h, and 0.54 g of amphoteric polyionic liquid monomer was dried at 55° C. for 18 h.

[0075] The above-mentioned inorganic filler, poly(vinylidene fluoride-co-hexafluoropropylene), amphoteric polyionic liquid monomer, 0.27 g of lithium bis(trifluoromethanesulfonyl)imide and 4 mL of N-methylpyrrolidone were mixed, and ultrasonic treatment was performed at a frequency of 40 kHz for 10 h to obtain a precursor solution; 0.01 g of N,N-methylenebisacrylamide and 0.03 g of azobisisobutyronitrile were mixed with the precursor solution, and stirred at a speed of 550 r / min at room temperature for 1 h in the absence of oxygen and water to obtain a reaction solution.

[0076] 60 μL of the reaction solution was dripped onto the NCM622 positive electrode material at a rate of 0.8 drops / s, and placed at 70°C for in-situ polymerization and curing for 3 hours to obtain a high-voltage resistant composite solid electrolyte with a thickness of 250 μm.

[0077] Example 2

[0078] 0.10 g of lithium lanthanum zirconium tantalum oxide solid electrolyte (LLZTO) was placed in a ball mill, 7 mL of isopropanol was added, and wet ball milling was performed at a speed of 900 r / min for 12 h; the ball-milled material was first placed in a vacuum drying oven (vacuum degree of 1 bar) at 50 ° C for 16 h, and then calcined at 750 ° C for 8 h to obtain an inorganic filler.

[0079] 0.14 g of poly(vinylidene fluoride-co-hexafluoropropylene) (molecular weight 45500 Da) was dried at 50°C for 24 h, 0.40 g of amphoteric polyionic liquid monomer was dried at 50°C for 24 h, and 0.20 g of polyethylene glycol diacrylate (molecular weight 400 Da) was dried at 50°C for 24 h.

[0080] The above-mentioned inorganic filler, poly(vinylidene fluoride-co-hexafluoropropylene), amphoteric polyionic liquid monomer, polyethylene glycol diacrylate, 0.27 g of lithium bis(trifluoromethanesulfonyl)imide, and 5 mL of N-methylpyrrolidone were mixed, and ultrasonically treated at a frequency of 45 kHz for 8 hours to obtain a precursor solution; 0.01 g of N,N-methylenebisacrylamide and 0.03 g of azobisisobutyronitrile were mixed with the precursor solution, and stirred at a speed of 500 r / min at room temperature for 2 hours in an oxygen-free and water-free manner to obtain a reaction solution.

[0081] 100 μL of the reaction solution was dripped onto the NCM622 positive electrode material at a rate of 1 drop / s, and placed at 70°C for in-situ polymerization and curing for 3 h to obtain a high-voltage resistant composite solid electrolyte with a thickness of 380 μm.

[0082] Example 3

[0083] The NCM622 positive electrode material in Example 2 is replaced with a lithium iron phosphate positive electrode material, and the rest is the same as Example 2.

[0084] Example 4

[0085] 0.22 g of lithium lanthanum zirconium tantalum oxide solid electrolyte (LLZTO) was placed in a ball mill, 11 mL of isopropanol was added, and wet ball milling was performed at a speed of 700 r / min for 24 hours; the ball-milled material was first placed in a vacuum drying oven (vacuum degree of 1 bar) at 70°C for 8 hours, and then calcined at 650°C for 24 hours to obtain an inorganic filler.

[0086] 0.27 g of poly(vinylidene fluoride-co-hexafluoropropylene) (molecular weight 45500 Da) was dried at 60°C for 12 h, 0.27 g of amphoteric polyionic liquid monomer was dried at 60°C for 12 h, and 0.20 g of polyethylene glycol diacrylate (molecular weight 400 Da) was dried at 60°C for 12 h.

[0087] The above-mentioned inorganic filler, poly(vinylidene fluoride-co-hexafluoropropylene), amphoteric polyionic liquid monomer, polyethylene glycol diacrylate, 0.40g lithium bis(trifluoromethanesulfonyl)imide and 10mL N-methylpyrrolidone were mixed, and ultrasonically treated at a frequency of 30kHz for 8h to obtain a precursor solution; 0.01g N,N-methylenebisacrylamide and 0.03g azobisisobutyronitrile were mixed with the precursor solution, and stirred at a speed of 600r / min at room temperature for 0.5 in the absence of oxygen and water to obtain a reaction solution.

[0088] 100 μL of the reaction solution was dripped onto the NCM622 positive electrode material at a rate of 0.1 drop / s, and placed at 60°C for in-situ polymerization and curing for 3 h to obtain a high-voltage resistant composite solid electrolyte with a thickness of 400 μm.

[0089] Figure 1 The electrochemical window of the high-voltage composite solid electrolyte prepared in Examples 1, 2 and 4. Figure 1 It can be seen that the electrochemical window of the high-voltage resistant composite solid electrolyte of the present invention is relatively wide, between 1.5 and 5.4V.

[0090] Figure 2 This is a cycle performance diagram of the high-voltage composite solid electrolyte prepared in Example 2 when used in lithium-ion battery NCM622 at 25°C and 0.2C. Figure 2 It can be seen that when the high-voltage resistant composite solid electrolyte of the present invention is used for the lithium-ion battery NCM622, it has high cycle stability, and the specific capacity can still be maintained at 100 mAh / g after 300 cycles at 25°C and 0.2C, and the capacity retention rate reaches 67%.

[0091] Figure 3 This is a cycle performance diagram of the high-voltage composite solid electrolyte prepared in Example 3 when used in a lithium iron phosphate battery at 25°C and 0.2C. Figure 3 It can be seen that the high-voltage composite solid electrolyte of the present invention has high cycle stability and capacity retention rate when used in lithium iron phosphate batteries, and the capacity retention rate after 300 cycles at 25°C and 0.2C reaches 77%.

[0092] Example 5

[0093] 0.11 g of lithium lanthanum zirconium oxide solid electrolyte (LLZO) was placed in a ball mill, 7 mL of isopropanol was added, and wet ball milling was performed at a speed of 900 r / min for 12 h; the ball-milled material was first placed in a vacuum drying oven (vacuum degree of 1 bar) at 50°C for 16 h, and then calcined at 750°C for 8 h to obtain an inorganic filler.

[0094] 0.54 g of poly(vinylidene fluoride-co-hexafluoropropylene) (molecular weight 45500 Da) was dried at 50°C for 24 h, 0.81 g of amphoteric polyionic liquid monomer was dried at 50°C for 24 h, and 0.30 g of polyethylene glycol diacrylate (molecular weight 400 Da) was dried at 50°C for 24 h.

[0095] The above-mentioned inorganic filler, poly(vinylidene fluoride-co-hexafluoropropylene), amphoteric polyionic liquid monomer, polyethylene glycol diacrylate, 0.165 g lithium hexafluorophosphate, and 33 mL dimethyl sulfoxide were mixed, and ultrasonically treated at a frequency of 45 kHz for 8 hours to obtain a precursor solution; 0.02 g ethoxylated trimethylolpropane triacrylate and 0.055 g azobisisobutyronitrile were mixed with the precursor solution, and stirred at a speed of 500 r / min at room temperature for 2 hours in an oxygen-free and water-free manner to obtain a reaction solution.

[0096] 80 μL of the reaction solution was dripped onto the lithium iron phosphate positive electrode material at a rate of 1 drop / s, and placed at 80° C. for in-situ polymerization and curing for 0.5 h to obtain a high-voltage resistant composite solid electrolyte with a thickness of 380 μm.

[0097] Example 6

[0098] 0.10 g of lanthanum lithium titanate solid electrolyte was placed in a ball mill, 6.6 mL of isopropanol was added, and wet ball milling was performed at a speed of 800 r / min for 20 h. The ball-milled material was first placed in a vacuum drying oven (vacuum degree of 1 bar) at 60°C for 12 h, and then calcined at 700°C for 16 h to obtain an inorganic filler.

[0099] 0.04 g of poly(vinylidene fluoride-co-hexafluoropropylene) (molecular weight 45500 Da) was dried at 55° C. for 18 h, and 0.06 g of amphoteric polyionic liquid monomer was dried at 55° C. for 18 h.

[0100] The above-mentioned inorganic filler, poly(vinylidene fluoride-co-hexafluoropropylene), amphoteric polyionic liquid monomer, 0.02 g of lithium difluorooxalatoborate, and 1.6 mL of N,N-dimethylformamide were mixed, and ultrasonically treated at a frequency of 40 kHz for 10 h to obtain a precursor solution; 0.001 g of 2-phenoxyethyl acrylate and 0.005 g of azobisisobutyronitrile were mixed with the precursor solution, and stirred at a speed of 550 r / min at room temperature for 1 h in the absence of oxygen and water to obtain a reaction solution.

[0101] 60 μL of the reaction solution was dripped onto the NCM622 positive electrode material at a rate of 0.8 drops / s, and placed at 70°C for in-situ polymerization and curing for 5 hours to obtain a high-voltage resistant composite solid electrolyte with a thickness of 300 μm.

[0102] The high-voltage composite solid electrolyte prepared by the present invention has a wide electrochemical window, can operate between 1.5 and 5.4 V, can be used in combination with a high-voltage positive electrode and lithium metal, and can exhibit excellent cycle stability at room temperature or even in a low-temperature environment.

[0103] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a high-voltage composite solid electrolyte, characterized in that: The following steps are included: (1) mixing a polymer, an inorganic filler, a lithium salt and a solvent to obtain a precursor solution; (2) mixing a precursor solution, a cross-linking agent and an initiator to obtain a reaction solution; (3) solidifying the reaction solution to obtain a high-voltage resistant composite solid electrolyte; The polymer comprises one or more of poly(vinylidene fluoride-co-hexafluoropropylene), polyethylene glycol diacrylate and amphoteric polyionic liquid monomers.

2. The preparation method according to claim 1, characterized in that: The inorganic filler comprises one or more of a lithium lanthanum zirconium oxide solid electrolyte, a lithium lanthanum titanate solid electrolyte, and a lithium lanthanum zirconium tantalum oxide solid electrolyte; The lithium salt comprises one or more of lithium perchlorate, lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium trifluoromethanesulfonate and lithium bis(trifluoromethanesulfonylimide); The solvent is dimethyl sulfoxide, tetrahydrofuran, N-methylpyrrolidone, N,N-dimethylformamide or acetonitrile; The crosslinking agent is ethoxylated trimethylolpropane triacrylate, N,N-methylenebisacrylamide or 2-phenoxyethyl acrylate; The initiator is azobisisobutyronitrile.

3. The preparation method according to claim 1 or 2, characterized in that: The mass volume ratio of the polymer and the solvent is 1g:1-20mL, the mass ratio of the polymer and the inorganic filler is 1-20:1, the mass ratio of the polymer and the lithium salt is 1-10:1, the mass ratio of the polymer and the cross-linking agent is 70-85:1, and the mass ratio of the polymer and the initiator is 20-30:

1.

4. The preparation method according to claim 3, characterized in that: The curing temperature in step (3) is 60-80° C. and the curing time is 1.5-6 hours.

5. The preparation method according to claim 1 or 4, characterized in that: The structural formula of the amphoteric polyionic liquid monomer is: Wherein, R1 is a carbon chain having 1 to 10 carbon atoms; R2 is a carbon chain having 1 to 10 carbon atoms or hydrogen.

6. The preparation method according to claim 5, characterized in that: The preparation method of the amphoteric polyionic liquid monomer comprises the following steps: 1) mixing alkyl sultone and toluene to obtain a solution I; Mixing 1-vinylimidazole and acetonitrile to obtain solution II; 2) adding solution I dropwise to solution II to react and obtain a solid product; 3) Drying the solid product to obtain the amphoteric polyionic liquid monomer.

7. The preparation method according to claim 6, characterized in that: In step 1), the mass volume ratio of the alkyl sultone and toluene is 10-20 g: 5-13 mL, and the mass volume ratio of the 1-vinylimidazole and acetonitrile is 5-15 g: 30-40 mL; in step 2), the volume ratio of the solution I and the solution II is 5-13: 30-40.

8. The preparation method according to claim 6 or 7, characterized in that: Step 2) The dropping speed is 0.3 to 1 drop / s; the reaction temperature is 45 to 60°C, the reaction time is 1.5 to 3 hours, and stirring is performed during the reaction at a speed of 500 to 600 r / min; Step 3) The drying temperature is 50 to 60°C, and the drying time is 24 to 48 hours.

9. The high-voltage composite solid electrolyte prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The thickness of the high-voltage composite solid electrolyte is 200-500 μm.

10. Use of the high-voltage resistant composite solid electrolyte according to claim 9 in lithium-ion batteries.

Citation Information

Patent Citations

  • Zwitter-ion-containing high-conductivity electrolyte, preparation method and battery prepared from zwitter-ion-containing high-conductivity electrolyte

    CN115189019A

  • Ionic liquid polymer solid electrolyte and preparation method and application thereof

    CN118184881A

  • Anode Particulates or Cathode Particulates and Alkali Metal Batteries

    US20190165374A1

Cited By

  • Binder, binder liquid, electrode mixture, electrode, intermediate layer, and battery

    WO2025204838A1